Предмет: Алгебра,
автор: Аноним
система уравнений.
двойная замена переменных
{ (x^2+1)(y^2+1)=10
{ (x+y)(xy-1)=3
Ответы
Автор ответа:
0
(xy)^2+1+x^2+y^2=10
(x+y)(xy-1)=3
(xy)^2+(x+y)^2-2xy=9
x+y=t
xy=s
t(s-1)=3 t=3/(s-1)
s^2+t^2-2s=9
s(s^3-4s^2-4s+16)=0
s=0 s=2 s^2-2s-8=0
s=4 s=-2
-2 ; 0; 2; 4; = xy
-1 ; -3 ; 3; 1 = x+y
(-2;1)
(1;-2)
(0;-3)
(-3;0)
(2;1)
(1;2)
нет решений
ответ
(-2;1) (1;-2) (0;-3) (-3;0) (2;1) (1;2)
Похожие вопросы
Предмет: Русский язык,
автор: polatovagulmira20
Предмет: История,
автор: daramartin0809
Предмет: Английский язык,
автор: oli0823
Предмет: Геометрия,
автор: cr9